Relationship between bully’s behaviour and parenting styles amongst primary school students - Hassan, Norlizah Che; S. H., Ee (Universiti Putra Malaysia Press, 2015)
This study was done to examine bully’s behavior among elementary school children, as well as to determine differences in parenting styles by parents and targeted child gender. This study involves 270 students of elementary school aged 11 years old. Result suggested that, both male and female school children were likely to perform verbal aggression. Males reacted more aggressive in three forms of bullying (verbal, physical, and indirectly) than females. The findings reveal that respondents’ father and mother practice authoritarian and permissive style to their sons, as compared to their daughters. While, effects of authoritative style for both father and mother are higher on females, as compared to males. Pearson correlation shows a significant positive low relationship between bully behaviour, and authoritarian and permissive parenting style, but there is no significant relationship between bully behaviour and authoritative parenting style. Overall, there is a significant negative low relationship between bully’s behaviour and parenting styles. Possible reasons for this phenomena and measures was discussed in relation to bully’s and parenting styles.